Iterative arrays with limited nondeterministic communication cell - Buchholz, Thomas; Klein, Andreas; Kutrib, Martin; Justus Liebig University Giessen (My University, 1999)
Iterative arrays with restricted nondeterminism are investigated. Non-determinism is provided for the distinguished communication cell only. All the other cells are deterministic ones. Moreover, the number of allowed nondeterministic state transitions is limited dependent on the length of the input. It is shown that the limit can be reduced by a constant factor without affecting the language accepting capabilities, but for sublogarithmic limits there exists a infinite hierarchy of properly included realtime language families. Finally we prove several closure properties of these families.
Keywords: ddc:004